1989
DOI: 10.3109/00016348909021021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Menstrual History and Basal Body Temperature with Early Fetal Growth by Ultrasound in Diabetic Pregnancy

Abstract: The time of ovulation and conception of 24 insulin-dependent (Type I) diabetic women was estimated by monitoring the basal body temperature (BBT). The mean (+/- SD) duration of the menstrual cycle was 28 (+/- 2) days. Conception occurred, on the average, on the 18th day of the cycle. The fetal crown-rump length was measured by ultrasound scan every 2 weeks between 6 and 14 weeks of pregnancy. When menstrual history was used for dating, there was an apparent early fetal growth delay by a mean of 4 days. When th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…These findings were based on examinations of crown–rump length 7–14 weeks after the LMP, compared with the expected length calculated from the LMP. Other small studies found no such growth delay, or explained an apparent delay with menstrual or ovulatory disturbances . Focus in these studies was partly on a possible prediction of excess malformation risk in fetuses with growth delay in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were based on examinations of crown–rump length 7–14 weeks after the LMP, compared with the expected length calculated from the LMP. Other small studies found no such growth delay, or explained an apparent delay with menstrual or ovulatory disturbances . Focus in these studies was partly on a possible prediction of excess malformation risk in fetuses with growth delay in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…To explain this discrepancy, it has been suggested that the biphasic observations were based on an apparent retardation, due to the effects of an average 4-day increase in the follicular phase of the menstrual cycle in women with IDDM (Hieta-Heikurainen and Teramo, 1989). Thus, the fetuses were not retarded, but normal for their true approximately one-half week smaller gestational ages.…”
Section: Outcomes For the Fetus Of A Diabetic Pregnancymentioning
confidence: 99%
“…Alternatively, it has been previously suggested that with maternal diabetes the embryos may be constitutionally smaller (Reece et al, 1990b). These alternative views suggest that exposure to maternal diabetes may result in significantly different growth dynamics in the fetus from conception (Mulder and Visser 1991), and/or that exposure may shift the developmental curve of normal fetal growth to the right, with a time lag in developmental progress (Hieta-Heikurainen and Teramo, 1989). They point to the importance of controlling for gestational day of age as a covariate in statistical analyses.…”
Section: Outcomes For the Fetus Of A Diabetic Pregnancymentioning
confidence: 99%
“…They suggest from this evidence that poor control causes growth delay, but they still had an average delay of five days in those attending the diabetes hospital and conclude that in early diabetic pregnancy most fetuses are smaller than normal. Our patients were well or moderately controlled (normal nondiabetic HbA, in our laboratory is 5.8‐8.0%), and in our previous study there were only two poorly controlled patients; however, the average HbA, in the study by Hieta‐Heikurainen & Teramo (1989) was high, and in Cousins et al (1988) study, which included two abnormal fetuses, very high. It is likely that less well‐controlled diabetics have less regular cycles (Adcock et al 1994).…”
Section: Discussionmentioning
confidence: 48%
“…The six‐day discrepancy in one patient may be due to slightly inaccurate dating of ovulation using basal body temperature (Lenton et al 1977). There have been several studies published from different centres using a variety of methods of identifying the time of ovulation (Whittaker et al 1983; Steel et al 1984; Cousins et al 1988; Hieta‐Heikurainen & Teramo 1989) (Table 2). None of these studies has shown a difference of more than five days between scan dates and ovulation dates.…”
Section: Discussionmentioning
confidence: 99%